The Effect of 37% Phosphoric Acid Etchant, Bonding Agent and 70% Ethyl Alcohol on the Permeability of Nitrile Gloves/Cyreyn Jeal D. Santos and Rheena Joyce M. Tan. - Santos, Cyreyn Jeal D.; Tan, Rheena Joyce M.
INTRODUCTION: Gloves are part of the Personal Protective Equipment (PPE) that is vital in Dentistry for infection control. Vinyl, latex, and nitrile gloves are the most common types used, but there has been increasing recommendation for nitrile gloves due to the insufficiency of vinyl, and the increasing incidences of latex allergy despite non-powdered latex gloves. Hence, the importance of nitrile gloves as a protective barrier has intensified. Moreover, the integrity of gloves is questioned as it is exposed to dental materials and chemicals during dental procedures.